Big Data Approach for Weather Based Crop Insurance - Mangani, K.P; Kousalya, R (International Journal of Computer Sciences and Engineering, 2025)
In Agriculture sector where the government and their supporting agencies need to make numerable decisions based on the adverse weather factors and the reports submitted to them. One of the essential issue is the crop insurance based on weather factors. Data mining and analytics techniques are necessary approaches for accomplishing practical and effective solutions for this problem. In addition to adverse weather conditions, variability in crop yields, input levels and damage statistics for a pre-identified crop or variety of crops information which are more relevant for farmers to make use of critical farming decisions. This paper focuses on the analysis of categories of data in agriculture and provides the bigdata approach for crop insurance data base on the background of insurance industry reform combined with the analytics technologies and to create the awareness of crop insurance scheme through online self-service weather insurance for farmers .Big Data involves the Multi criteria decisions involving spatially identifying the affected areas,Weather data, Farmer interviews, dry and wet management areas, Expert opinion of local extension officers, historical weather data, website data would help insurance companies to select the crop insurance products